Neuroimaging in Developmental Coordination Disorder - GÜNAY YAZICI, CANAN; ACAR, GÖNÜL; POLAT, MİNE GÜLDEN (My University, 2021)
Developmental coordination disorder (DCD) is a neuromotor disorder of unknown etiology characterized by motor skill disorder, which significantly inhibits the child’s ability to perform daily living activities and affects psychosocial well-being. DCD is one of the least understood and studied neuromotor disorders, and little is known about the neural mechanisms underlying motor impairment. This makes it difficult to understand why children with DCD have difficulty in learning motor skills and what is the best intervention to optimize motor functions. With the further development of neuroimaging techniques, the number of neuroimaging studies to understand the underlying mechanisms in children with DCD has increased in recent years. Results from these studies suggest that children with DCD activate different regions of the brain during functional tasks and show differences in white matter microstructure, cerebellum, basal ganglia, parietal lobe, and parts of the frontal lobe (medial orbitofrontal cortex and dorsolateral prefrontal cortex) compared with typically developing children. We believe that these neuroimaging data obtained from numerous studies will contribute to the explanation of neural mechanisms related to impaired motor function in children with DCD.